Peran Media Sosial sebagai Sarana Promosi dalam Meningkatkan Daya Tarik Pengunjung di Serdika Pavilion Berastagi - Josua Sitanggang; Ingan Ukur Br Sitepu; Frans Antoni Sihite; Menanti Br Sembiring (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine and analyze the role of social media, specifically TikTok, as a promotional tool in increasing visitor appeal at Serdika Pavilion Berastagi, Karo Regency, North Sumatra. The research was motivated by the increasingly fierce competition in the accommodation business in the Berastagi tourist area, necessitating effective promotional strategies to attract visitors. Social media was chosen because of its ability to reach a wide audience quickly and interactively.This study employed a qualitative approach with descriptive methods. Data were collected through interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was tested using triangulation The results indicate that social media plays a significant role in increasing visitor appeal. The use of TikTok through photo and video content showcasing the accommodation's facilities, ambiance, location, and pricing information successfully attracted potential visitors. Furthermore, consistent uploads and active responses to comments and messages helped build trust and a positive image of the accommodation. This strategy encouraged increased visitor interest in obtaining information, visiting, and choosing Serdika Pavilion Berastagi as a place to stay. Based on the research results, it can be concluded that social media is an effective promotional tool for increasing visitor attraction. However, management still needs to improve content creativity and promotional consistency to achieve optimal and sustainable results.